2006
DOI: 10.1111/j.1572-0241.2006.00890.x
|View full text |Cite
|
Sign up to set email alerts
|

Office-Based Unsedated Small-Caliber Endoscopy Is Equivalent to Conventional Sedated Endoscopy in Screening and Surveillance for Barrett's Esophagus: A Randomized and Blinded Comparison

Abstract: Office-based unsedated small-caliber endoscopy is technically feasible, well tolerated, and accurate in screening for Barrett's esophagus, despite yielding a smaller biopsy specimen. This approach bears the potential to eliminate the infrastructure and cost required for intravenous sedation in this application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
114
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(120 citation statements)
references
References 34 publications
1
114
0
5
Order By: Relevance
“…Although in our study the sensitivity was lower (67%), the specificity was 95% for the diagnosis of BE. In another study, Jobe et al [12] found that, in a cohort of 274 eligible adults scheduled for endoscopic screening for gastroesophageal reflux symptoms or surveillance of BE in a tertiary care center, the prevalence of BE was 26% using conventional endoscopy and 30% using unsedated small-caliber endoscopy (P = 0.503). In this study, the level of agreement between the two approaches was "moderate" (κ = 0.591).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although in our study the sensitivity was lower (67%), the specificity was 95% for the diagnosis of BE. In another study, Jobe et al [12] found that, in a cohort of 274 eligible adults scheduled for endoscopic screening for gastroesophageal reflux symptoms or surveillance of BE in a tertiary care center, the prevalence of BE was 26% using conventional endoscopy and 30% using unsedated small-caliber endoscopy (P = 0.503). In this study, the level of agreement between the two approaches was "moderate" (κ = 0.591).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several endoscopy techniques have recently been developed as alternatives and less invasive diagnostic tools for evaluating GERD and esophageal varices [12][13][14][15][16]20] . Here, in this study we have shown that unsedated esophagoscopy using a novel disposable transnasal esophagoscope (E.G.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17] The major advantage of TNO is that it can be performed without the need for intravenous sedation or general anaesthesia, which is required for oesophagogastroduodenoscopy or rigid endoscopy respectively. This has profound implications as both sedation and anaesthesia carry significant risks; it is estimated that 0.6% of patients receiving sedation develop a cardiopulmonary event.…”
Section: Sanyaolu Jemah Stew Ingrams the Role Of Transnasal Oesophagomentioning
confidence: 99%